The differences of kinematic parameters pole vault between male and female finalists World Championship in Daegu, 2011 - Pavlovic, R.; Vrcic, M.; Savic, V.; Skrypchenko, I.; Németh, Z.; Khafagy, A. (European Journal of Physical Education and Sport Science, 2019)
Kinematic parameters often crucially influence the performance in athletic disciplines. This is especially evident for top athletes who have almost identical morphological, motor and functional parameters. The differences that affect the sporting result are generally attributed to a better performance technique that is often the consequence of the different values of the individual's kinematic parameters. This study analyzes the differences between the defined kinematic parameters in the discipline Pole vault. The sample included 16 men and women athletes who competed in the finals of the World Championships (Daegu, 2011) and a total of 9 kinematic parameters were selected. The results were obtained by applying the T-test module for small independent samples, confirming the differences between men and women's finalists in Daegu, 2011. Statistically significant differences were recorded eight of nine kinematic parameters (about 89%). Significant differences were recorded in the following kinematic parameters: total run-up distance (T=5,312; p<0,01), number of steps (T=2,712; p<0,05), average step length (T=6,725; p<0,01), VA (T=18,430; p<0,01), AP (T=8,326; p<0,01); ¹average step length last (T=2,662; p<0,01); ²average step length last (T=8,303; p<0,01), ³average step length last (T=8,362; p<0,01).